Who prefers to stay? Individual and institutional factors supporting immobility among minority Hungarian higher education students - Sütő, Zsuzsanna (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2025)
Based on the migration models proposed by J. Carling, de Haas, and K. Schewel, we examine the immobility aspirations of minority and majority Hungarian students in Central Europe. Our aim is to identify individual as well as institutional factors that we hypothesise support students in developing their immobility aspirations. We analyse empirical data collected through a survey in 2019 among students of Hungarianlanguage higher education institutions in Hungary, Ukraine, Romania, Slovakia, and Serbia (N = 2,210). The results of multivariate and logistic regression analyses show that the development of immobility aspirations is supported by socio-demographic factors and social networks, as well as by institutional and academic factors, such as training programmes preparing students for local professions, and a greater degree of trust in the higher education institution and role partners.
Keywords: aspiration/ability model; družbeno sožitje; higher education; izobraževalna infrastruktura; kulturna inkluzivnost; migration; minority students; raznolikost; vključenost